2018
DOI: 10.15540/nr.5.2.57
|View full text |Cite
|
Sign up to set email alerts
|

Combining frontal gamma asymmetry neurofeedback with virtual reality: A proof of concept case study

Abstract: The current proof-of-concept case study was designed to determine if a consumer-grade neurofeedback system (Muse) could be used in conjunction with specially designed virtual reality (VR) environments (Positivity by Healium) to impact gamma frontal asymmetry as well as create positive changes in mood states. Four firefighters served as subjects and completed pre-post mood rating scales as well as 19-channel EEG recordings. An examination of sLORETA frontal lobe ROIs demonstrated a postintervention gamma asymme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Here, our results confirmed our hypothesis as there was a significantly higher left than right frontal activity in the gamma frequency band during unplanned conditions, relative to planned choices. As some recent studies suggested ( Ramsøy et al, 2018 ; Tarrant and Cope, 2018 ), we found a greater gamma asymmetry score for unplanned choices compared to planned choices. These findings provide new insights into the role of gamma frequency band activity in decision making particularly in consumer neuroscience.…”
Section: Discussionsupporting
confidence: 83%
“…Here, our results confirmed our hypothesis as there was a significantly higher left than right frontal activity in the gamma frequency band during unplanned conditions, relative to planned choices. As some recent studies suggested ( Ramsøy et al, 2018 ; Tarrant and Cope, 2018 ), we found a greater gamma asymmetry score for unplanned choices compared to planned choices. These findings provide new insights into the role of gamma frequency band activity in decision making particularly in consumer neuroscience.…”
Section: Discussionsupporting
confidence: 83%
“…Past studies have shown that meditation practice could induce a greater proportion of activity in the left frontal region, particularly in the alpha band, which was associated with positive, approach-oriented emotional states [4,19,20]. Similarly, neurofeedback interventions that shift the frontal hemispheric asymmetry toward left activation have been shown to induce improvements in mood and alleviation of anxiety and depression symptoms [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…In this study we used Healium TM , the world’s first evidence-based 23,24 virtual reality experience powered solely by brainwaves. 25 This study delivered the Healium TM software using an Oculus Go virtual reality headset.…”
Section: Methodsmentioning
confidence: 99%